Effects of intermittent pneumatic compression device on the improvement of tissue oxygen saturation and fluid clearance at the compression site - Aoyagi, M.; Komatsu, T.; Togashi, I.; Iriguchi, K.; Nagao, M.; Kubota, A.; Izawa, H.; Someya, Y.; Oshio, K.; Takazawa, Y. (Frontiers in Physiology, 2026)
Introduction: Intermittent pneumatic compression devices (IPCDs) facilitate post-exercise recovery by increasing tissue oxygen saturation (rSO2) and reducing intramuscular interstitial fluid. However, limited evidence exists on time-course changes of these physiological responses during the intervention. This study aimed to examine the effects of IPCD use on rSO2 and fluid content in the lower limbs.